Use and knowledge of single dose activated charcoal: A survey of Australian doctors. (23rd August 2016) - Corcoran, Gabriela; Chan, Betty; Chiew, Angela
Abstract: Objective: The use of single dose activated charcoal (SDAC) as a means of gastric decontamination is declining. The present study examined the potential use of SDAC in common overdose scenarios by Australian emergency doctors, compared with clinical toxicologists and current guidelines. Methods: We conducted a cross‐sectional survey of emergency doctors and toxicologists on the use of SDAC. The survey covered demographic data, education and previous use of SDAC and six clinical scenarios. The scenarios selected included agents not bound to SDAC, sustained‐release preparations and ingestions at varying time points. Statistical calculations were performed using Fisher's exact test. Results: There were 397 emergency doctors and 20 toxicologists who responded to the survey. Seventy‐one per cent ( n = 280/397) of emergency doctors indicated they had received some education on decontamination. Eighty‐three per cent ( n = 331/397) had administered SDAC during their medical career, 29% ( n = 117/397) within the past year. There was a significant difference in responses between emergency doctors and toxicologists in two scenarios; a toxic paracetamol ingestion presenting within 1 h ( P = 0.009) and verapamil ingestion in a 3 year old boy ( P = 0.001). Toxicologists were more likely to administer SDAC in these scenarios, 89% ( n = 16/18) and 88% ( n = 15/17), respectively, compared with 52% ( n = 197/381) and 43% ( n = 158/371) of emergency doctors. Conclusions: Our study showed that there is a significant variation in the use of SDAC between toxicologists and emergency doctors in some scenarios. Clinical toxicologists are more likely to administer SDAC in certain overdose settings. It is essential to provide education on the benefits versus actual risks of SDAC in acute poisoning so that doctors will understand when to administer SDAC or seek further advice.